Enhancement of Sia-lb1 antigenicity by sulphur-containing substituents at C-5 of free N-acetylneuraminic acid - Roelcke, Dieter; Leo, Albrecht; Brossmer, Reinhard (Beiträge zur Infusionstherapie und Transfusionsmedizin, 1997)
The Sia-lb1 epitope, recognized by anti-Sia-lb1 cold agglutinins, is unique since it is represented by the alpha-N-acetylneuraminic acid (alpha NeuNAc) monosaccharide. Chemical modifications of the chain at C-5 of alpha NeuNAc have shown that the natural 2-carbon and the artificial 3-carbon chains are optimal for anti-Sia-lb1 binding. Sia-lb1 antigenicity of alpha NeuNAc could be tenfold enhanced by replacement of the carbonyl oxygen by sulphur. The structural requirements of the Sia-lb1 epitope for optimal antibody binding were identified.